The impact of social capital and government support on farmers’ willingness to pay for road governance: a case study of rural road governance in China - Zhou, Xiaoli; Han, Mingyang; Wang, Yunxuan (Frontiers in Environmental Science, 2025)
The global environmental governance landscape is currently confronted with complex and pressing challenges, while rural road environments play a crucial role in providing essential services to rural ecosystems, making them a key factor in the success or failure of governance. Based on the 2018 China Labor Dynamic Survey Database (CLDS), this article approaches the issue from the perspective of rural environmental governance and uses the informal social networks of rural farmers as a starting point to construct an analytical framework for social capital and farmers’ willingness to engage in environmental governance. Additionally, to examine the close link between welfare policies and farmers’ participation in public affairs, this article specifically focuses on the potential moderating effect of government support (agricultural subsidies) and uses the instrumental variable method to mitigate its endogeneity. The study shows that: (1) Both improvements in social networks and social trust can promote farmers’ willingness to engage in environmental governance. However, in the process of social participation, exposure to cutting-edge green technologies is essential to precisely activate individuals’ willingness to engage in environmental governance. (2) In promoting individual farmer participation in environmental protection public affairs, it is crucial to emphasize the incentives provided by welfare policies, increase agricultural subsidies, and expand their depth and breadth of coverage. (3) Government departments should enhance the industrial vitality in the northeastern regions, accelerate industrial transformation, invigorate economic activity, and prevent population loss from causing disruptions in villages. In the western regions, context-specific cultural intervention measures should be developed. Through long-term and continuous “cultural governance” practices, a bottom-up, progressive approach should be adopted to stimulate public enthusiasm for participation in non-interest-driven public affairs and achieve self-sufficiency in the cultural field.